Methods For Diagnosing DrugResistant Tuberculosis - Makhsumova Dinora Kamolovna (Genius Journals, 2024)
The widespread prevalence of drug-resistant tuberculosis is a global problem and can negatively affect the tuberculosis situation on a global scale. Rapid diagnosis of the disease and early initiation of effective treatment based on the selection of personalized chemotherapy regimens are the basis for preventing the spread of tuberculosis. Microbiological methods are of particular importance for the diagnosis of tuberculosis, which make it possible to substantiate the etiology of the process and determine the drug sensitivity of the pathogen. The review examines current and developing methods for the microbiological diagnosis of tuberculosis, including classical microbiological and modern molecular genetic tests
Keywords: Mycobacterium tuberculosis; drug resistance; molecular genetic methods; culture diagnostics